Association of P2RX7 functional variants with localized aggressive periodontitis. (10th July 2019) - Harris, Theodore H.; Wallace, Margaret R.; Huang, Hong; Li, Hua; Mohiuddeen, Azeem; Gong, Yan; Kompotiati, Theodora; Harrison, Peter; Aukhil, Ikramuddin; Shaddox, Luciana M.
Abstract: Objective: The purpose of this study was to investigate involvement of the P2X7 receptor in the rare condition, localized aggressive periodontitis. Material and methods: Peripheral blood from 220 African Americans (103 with localized aggressive periodontitis and 117 healthy unrelated controls) was stimulated with lipopolysaccharide from E   coli and Porphyromonas gingivalis . P2RX7 single nucleotide polymorphisms rs208294 (H155Y), rs1718119 (T348A), rs2230911 (T357S) and rs3751143 (E496A) were genotyped in 103 localized aggressive periodontitis patients and 117 healthy unrelated subjects. We examined genetic association between four P2RX7 single nucleotide polymorphisms and localized aggressive periodontitis, and tested for correlations between the single nucleotide polymorphisms and inflammatory response to lipopolysaccharide in blood samples from these patients. Results: A significant association with localized aggressive periodontitis was observed with rs1718119 A (Thr) allele ( P  = 0.0063, odds ratio = 1.904) and with a haplotype containing this allele ( P  = 0.0075). Additionally, significant correlations with these data were found: the rs1718119 G allele correlated with greater production of IL‐6, IL‐2 and GM‐CSF; the C (His) allele of rs208294 correlated with lower levels of IL‐12p40; and the C (Thr) allele of rs2230911 correlated with greater levels of G‐CSF. Conclusion: The data from these analyses support a possible biological relationship between P2RX7 genetic variants and inflammatory response in localized aggressive periodontitis patients.